2011
DOI: 10.1007/s00213-011-2297-1
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT6 receptor agonist EMD 386088 produces antidepressant and anxiolytic effects in rats after intrahippocampal administration

Abstract: The results of the present study demonstrate that the 5-HT6 agonist produces antidepressant- and anxiolytic-like effects and that the hippocampus could be one of the brain regions involved in this action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 45 publications
(55 reference statements)
6
33
0
Order By: Relevance
“…Values represent the mean ± SEM and were analyzed by two-way ANOVA followed by Bonferroni's post hoc test: *p < 0.001 relative to Sham control, # p < 0.001 relative to OB control, N = 6-7 antidepressant-like effect, mediated by stimulation of 5-HT 6 receptors, seems to be specific, since EMD 386088 did not affect rats' activity, as measured on the OF apparatus. Our results are in line with the findings of the study by Nikiforuk et al (2011) who reported a potential antidepressant effect of EMD 386088 following its acute i.h. administration to rats.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Values represent the mean ± SEM and were analyzed by two-way ANOVA followed by Bonferroni's post hoc test: *p < 0.001 relative to Sham control, # p < 0.001 relative to OB control, N = 6-7 antidepressant-like effect, mediated by stimulation of 5-HT 6 receptors, seems to be specific, since EMD 386088 did not affect rats' activity, as measured on the OF apparatus. Our results are in line with the findings of the study by Nikiforuk et al (2011) who reported a potential antidepressant effect of EMD 386088 following its acute i.h. administration to rats.…”
Section: Discussionsupporting
confidence: 93%
“…injection of EMD 386088, blocked its reduction of immobility and increase swimming behavior. Therefore, the authors concluded that the activation of 5-HT 6 receptors might participate in the potential antidepressant activity of EMD 386088 and the hippocampus might be one of the brain structures involved in this action (Nikiforuk et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies found an advantageous 5-HT 6 -mediated GABA activation and suggested antagonists in the treatment of psychiatric disorders such as schizophrenia (Marsden et al 2011;Pouzet et al 2002;Vogt et al 2000). Both, agonists and antagonists, have been implicated in the treatment of depression (Kishi et al 2010;Nikiforuk et al 2011;Wesolowska 2010) and anxiety disorders (Wesolowska 2010) as well as feeding behavior and obesity (Heal et al 2008;Holenz et al 2006). Further, 5-HT 6 receptor genes have been linked to bipolar disorder (Vogt et al 2000).…”
Section: -Htmentioning
confidence: 99%